The Kyai's Leadership in Efforts to Maintain the Boarding School Tradition - Mohammad Afif Syafiudin; Chusnul Chotimah; Didin Sirojuddin; Saihul Atho Alaul Huda (SCHOOLAR: Social and Literature Study in Education, 2024)
The objectives of this research are: 1) To describe the leadership of kyai in preserving the social traditions of the Islamic boarding school Darun Najah Karangploso Malang. 2) To describe the leadership of kyai in preserving the scholarly traditions of Darun Najah Karangploso Malang Islamic boarding school. This research adopts a qualitative approach, specifically a descriptive type. Data collection methods include observation, interviews, and documentation. As for the data analysis process, researchers used a data analysis model initiated by Sugiono, which consists of 4 steps: data collection, data reduction, data display, conclusion drawing, and conclusion drawing/verification. The results of this research indicate that: 1) The social traditions of the Islamic boarding school Darun Najah Karangploso Malang are manifested through activities such as communal gatherings, admonitions, and thanksgiving events. These activities facilitate social interaction among students, between students and the community, and between students and religious teachers in a familial atmosphere. 2) The continuity of studying classical Islamic texts intensively and the utilization of traditional teaching methods such as recitation, discussion groups, memorization, and deliberation. These activities are intended to ensure that students preserve the knowledge they have acquired.